A COMPARISON OF ECONOMIC EFFICIENCY RATE IN THE JAJAR LEGOWO AND TEGEL PLANTING SYSTEMS: A CASE OF THE RICE FARMING IN EAST MANGGARAI REGENCY, INDONESIA - Willybrordus Lanamana; Imaculata Fatima (Faculty of Animal and Agricultural Science, Diponegoro University, 2022)
Escalating rice production through technical efficiency becomes an essential alternative as the extensification path is getting tough to take. Rice productivity declines while the consumption rate continues to rise. This study aims to analyze the technical, allocative, and economic efficiency rates of the Jajar Legowo and Tegel Planting Systems. Factors of efficiency are included in the research. The research was conducted in the village of Nanga Buntal, East Manggarai, a rice production centre district in the Province of NTT. Among 152 rice farmer respondents, 102 are from the Jajar Legowo planting system and 50 from the Tegel planting system. The stochastic frontier Cobb-Douglass method is used in data analysis. The allocation and economic efficiency are analyzed using the Stochastic frontier cost function. This analysis also uses multiple linear regression analysis. The average rates of technical, allocative, and economic efficiency of the Tegel planting system are respectively 72 %, 76 % and 56 %. These rates are lower than that of the Jajar Legowo Planting system (84 %, 86 %, and 73%). The periods of farming, land area, dummy of farmer group members, and the dummy of planting systems are factors that significantly and positively influence technical and allocative efficiency. Factors that negatively affect efficiency are farmers' age and credit access dummy. Further intensive training for the Jajar Legowo planting system is needed.